Angelus – prawdziwy portret grupowy w sztucznych dekoracjach - Nowakowski, Jacek (Slavia Occidentalis, 2011)
The article presents various semantic levels of the film of Lech Majewski entitled Angelus (2001). The author concentrates mainly on the history of Upper Silesia in the period between 1930–1950, the history of the occult commune and the painting society, the so-called “Janów Group”, as well as the relation sacred-profane, expressed by the references to the history of the Rosicrucian Order. Another context discussed in the article is the intersemioticism of the film (especially the relations between painting and film). The interpretation of the film takes into account the basic context that is the artistic activity of Lech Majewski.